2020
DOI: 10.1029/2019ea000950
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Speed of Shallow Seafloor Sediments in the Northern South China Sea and Their Correlations With Physical Parameters

Abstract: In this study, shear wave speed and related physical properties were measured for 21 seafloor sediment cores collected in the northern South China Sea. Results reveal that the shear wave speed in this study area ranges between 15.57 and 75.55 m/s and demonstrates a pattern of regional distribution. The sediment in the continental shelf area shows characteristics of high shear wave speed, high wet bulk density, low porosity, and large grain size. Contrarily, the sediment in the continental slope area exhibits c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Lu and Liang (1991) established the dual-parameter regression equations between the shear wave speed and the dual-parameter pair of unconfined compression strength and strength sensitivity of sediments and pointed out that the dual-parameter equations have higher correlation coefficients than the single-parameter equations. Kan et al (2020) established dual-parameter regression empirical equations of shear wave speed with porosity and average grain size at different frequencies based on data from the northern part of the South China Sea, and the correlation coefficient was significantly improved compared to the single-parameter empirical equation.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and Liang (1991) established the dual-parameter regression equations between the shear wave speed and the dual-parameter pair of unconfined compression strength and strength sensitivity of sediments and pointed out that the dual-parameter equations have higher correlation coefficients than the single-parameter equations. Kan et al (2020) established dual-parameter regression empirical equations of shear wave speed with porosity and average grain size at different frequencies based on data from the northern part of the South China Sea, and the correlation coefficient was significantly improved compared to the single-parameter empirical equation.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2005) provided a more detailed understanding of the physical and mechanical properties of submarine soils by exploring the properties of clay soils in the South Yellow Sea resource area as well as the size and characteristics of particles. On the basis of measured data on the shear wave velocity of submarine soil in the Yellow Sea, Kan et al (2014) found some correlation between soil shear wave velocity and physical and mechanical parameters. In addition, in situ testing on the mechanical properties of submarine soils has been widely carried out (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%